Multiple Organ Dysfunction Syndrome: Phytotherapeutic Evidences from Intestinal Ischemia – Reperfusion Models. (2023)
The gastrointestinal mucosa serves important barrier and defensive function against pathogenic bacteria, aggressive factors, and other inflammatory stimuli present within the lumen of the intestines. A variety of pathological and/or surgical conditions, known to produce intestinal ischemia-reperfusion injury (IIRI) (e.g., hemorrhagic shock, strangulated bowel, intussusception, and volvulus) has been associated with breaches in gut barrier integrity, increased barrier permeability, and translocation of viable enteric bacteria and their toxins into the portal and systemic circulation. The result of this trans-epithelial movement of enteric microbes and/or toxins is the generalized activation of various inflammatory mediators (e.g., cytokines, reactive oxygen species, leucocytes, and the complement system) in what is often described as the systemic inflammatory response syndrome (SIRS). One devastating consequence of IIRI and SIRS is widespread injury to remote organs, a condition often referred to as multiple organ dysfunction syndrome (MODS), which is the leading cause of mortality in critically ill patients, especially those in intensive care units. From the foregoing, it has been suggested that compounds that combine multiple activities such as antibacterial, anti-inflammatory, antioxidant, and immune-modulatory roles, may provide new approaches to the prevention and/or treatment of MODS. In this regard, medicinal herbs with their composite nature of bioactivities due to several inherent phytochemicals are being investigated at different levels for their benefits in modulating the pathophysiological mechanisms that give rise to MODS. With particular reference to animal models of IIRI, this chapter explores available experimental evidence of the potential prophylactic and/or therapeutic benefits of medicinal herbs in limiting remote organ dysfunction arising from gastrointestinal injury.